THE EFFECT OF INTELLECTUAL CAPITAL ON NON PERFORMING FINANCING AND IT’S IMPLICATION TOWARD FINANCIAL PERFORMANCE OF SHARIA COMMON BANKS - Sudiyatmoko, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This research aim to find out the influence element Intellectual Capital through Non Performing Financing (NPF) as the intervening variable to the Financial Performance (ROA) of Islamic banks registered in the financial services authority. The research population is all Syaria commercial banking companies in 2011-2017 periods. The statistic method has been done by using descriptive statistic and path analysis. The result of the research on Intellectual  Capital element consisting of  VACA (Value Added Capital Employed), VAHU (Value Added Human Capital) dan STVA (Structural Capital Value Added) shows that VAHU has insignificant and negative influence to Non Performing Financing (NPF) and significant and positive influence to the Financial Performance (ROA). STVA has insignificant and negative influence to Non Performing Financing (NPF) and insignificant and positive influence to the Financial Performance (ROA). VACA has significant and negative influence to Non Performing Financing (NPF) and significant and positive influence to the Financial Performance (ROA). The result of the research shows the magnitude of the indirect influence of Intellectual  Capital through Non Performing Financing (NPF) to the Financial Performance (ROA) is smaller than the magnitude of direct influence Intellectual  Capital to the Financial Performance (ROA)